2009
DOI: 10.1080/08897070903250019
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Meditation for Substance Use Disorders: A Systematic Review

Abstract: Relapse is common in substance use disorders (SUDs), even among treated individuals. The goal of this article was to systematically review the existing evidence on mindfulness meditation-based interventions (MM) for SUDs.The comprehensive search for and review of literature found over 2,000 abstracts and resulted in 25 eligible manuscripts (22 published, 3 unpublished: 8 RCTs, 7 controlled non-randomized, 6 noncontrolled prospective, 2 qualitative studies, 1 case report). When appropriate, methodological quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
189
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(207 citation statements)
references
References 82 publications
(424 reference statements)
4
189
1
7
Order By: Relevance
“…Given the core clinical symptoms of drug addiction [intoxication (impaired self-awareness), bingeing (loss of control), withdrawal, and craving] (12), mindfulness meditation may be helpful for coping with these addiction symptoms and with the accompanied negative emotion and stress reactivity. Prior studies have shown the preliminary efficacy of mindfulness meditation in treating several forms of addiction including alcohol, cigarettes, cocaine, amphetamines, marijuana, and opiates (26)(27)(28); however, as recent reviews have pointed out, the lack of randomization and active control groups indicate that these findings should be interpreted with caution (26,27).Our current study used a randomized controlled design with an active relaxation control (RT), as did our previous studies (20,(30)(31)(32), and we found a significant reduction in smoking and craving after 2 wk of IBMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the core clinical symptoms of drug addiction [intoxication (impaired self-awareness), bingeing (loss of control), withdrawal, and craving] (12), mindfulness meditation may be helpful for coping with these addiction symptoms and with the accompanied negative emotion and stress reactivity. Prior studies have shown the preliminary efficacy of mindfulness meditation in treating several forms of addiction including alcohol, cigarettes, cocaine, amphetamines, marijuana, and opiates (26)(27)(28); however, as recent reviews have pointed out, the lack of randomization and active control groups indicate that these findings should be interpreted with caution (26,27).Our current study used a randomized controlled design with an active relaxation control (RT), as did our previous studies (20,(30)(31)(32), and we found a significant reduction in smoking and craving after 2 wk of IBMT.…”
Section: Discussionmentioning
confidence: 99%
“…Although preliminary findings suggest mindfulness training shows some proof of efficacy in substance abuse, these studies are replete with limitations, including a lack of adequate control conditions, failure to randomize participants, and lack of assessment of biological markers of change. Thus, more rigorous and randomized controlled studies are warranted (26)(27)(28)(29). In a series of randomized controlled trials, it was found that a form of mindfulness meditation, integrative body-mind training (IBMT; Materials and Methods), reduces stress, increases positive emotion, and improves attention and self-control after a few hours of practice compared with the same amount of relaxation training (RT).…”
mentioning
confidence: 99%
“…Mindfulness practices have been incorporated into treatment for substance use disorder to improve remission maintenance Brewer et al, 2014;Garland et al, 2014;Witkiewitz, Bowen, Douglas, & Hsu, 2013;Zgierska et al, 2009). As a psychological construct, mindfulness can be described as a gentle, kind, and curious awareness of experience (Grossman, 2010).…”
Section: Mindfulness-based Treatment For Substance Use Disordersmentioning
confidence: 99%
“…Mind-body therapies included biofeedback, progressive muscle relaxation, meditation, guided imagery, hypnosis, tai chi, qi gong, and yoga non-judgmental acceptance of emotions, thoughts, and sensations in the ''present moment'' without the need for immediate action. 24 Energy healing uses objects or human touch with claims of changing the flow of energy through the body. Some examples of energy therapies include laying hands, reiki or healing touch, acupuncture, qi gong (tai chi), and magnetic therapy.…”
Section: Mind-body and Energy Therapiesmentioning
confidence: 99%